Atmospheric Visibility Measurements Based on a Low-Cost Digital Camera - Janeiro, Fernando M. (2008)
Atmospheric visibility is measured with a low-cost consumer digital camera. By using the dark pixel approach the visibility can be derived beyond the limits of the landmark detection method. The image gathering and processing is totally automated by computer controlling the digital camera. This approach is tested in different atmospheric conditions and the results are validated by measurements made by a human observer.